Design and analysis of compact metamaterial MIMO antenna for WLAN applications - Ullah, Sana; Lam, Phan Huu; Tung, Phan Duy; Tuan, Tran Sy; Hoa, Nguyen Thi Quynh (Vietnam Journal of Science and Technology, 2019)
A compact three-port metamaterial multiple-input-multiple-output (MIMO) antenna using complementary split-ring resonator (CSRR) loaded ground have demonstrated in order to miniaturize the size and improve the antenna performance. The antenna is designed on FR4 material and simulated by HFSS software. By loading CSRRs in the ground plane, the size reduction of 77% of the individual patch antenna element is achieved, which appeared to be the major reason for the obtained the compact MIMO antenna. Furthermore, the simulated results show that the proposed MIMO antenna achieves the total gain higher than 5 dB, the isolation less than -11 dB, the envelope correlation coefficient (ECC) value lower than 0.015, and the bandwidth of 100 MHz through the whole WLAN band from 2.4 GHz to 2.484 GHz, indicating promises for WLAN applications.